2021
DOI: 10.1002/vms3.477
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and risk factors for foot‐and‐mouth disease in cattle in Baghlan Province, Afghanistan

Abstract: Foot and Mouth Disease (FMD) is a highly contagious disease of cloven hoofed animals, which is a significant threat to livestock throughout the world, including Afghanistan (Rweyemamu et al., 2008). The disease has been endemic in Afghanistan for many years with three serotypes (A, O and Asia-1) being isolated from out-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
0
3
1
1
Order By: Relevance
“…in this study. This result contradicts previous studies, where frequent purchase of new animals has been identified as a risk factor for brucellosis ( 73 , 74 ) and FMD ( 75 ). In the present study, acquiring new animals for the herd was rare, and those who did mostly got them from other farmers in the village or from nearby villages.…”
Section: Discussioncontrasting
confidence: 99%
“…in this study. This result contradicts previous studies, where frequent purchase of new animals has been identified as a risk factor for brucellosis ( 73 , 74 ) and FMD ( 75 ). In the present study, acquiring new animals for the herd was rare, and those who did mostly got them from other farmers in the village or from nearby villages.…”
Section: Discussioncontrasting
confidence: 99%
“…Within the selected villages, 198 households/cattle-herds were randomly selected from a list of all herds ( n = 450) in these villages provided by local veterinary professionals (there are no official records of the exact number of herds present in the surveyed villages, however the local veterinary authorities, based on their experience, estimated there were 450 herds present in these villages). Details of the study setting, field methodology, and epidemiological terminology that describe the animal husbandry and veterinary services provided to the farmers in the study area were previously been explained in Osmani et al [ 8 ]. A questionnaire was administered at the same time as serological and socio-economic studies were performed.…”
Section: Methodsmentioning
confidence: 99%
“…In large flocks, diseases can be transmitted to other animals through close contact and sometimes due to compromised innate immunity resulting from management issues. 27 Similarly, poor health and/or body condition resulting from suboptimal or inadequate nutrition is a major factor contributing to the impaired functioning of innate and acquired immunity by decreasing the synthesis of T-and B-lymphocytes. 28,29 In conclusion, the seroprevalence results found in the current study indicate an alarming situation of FMD in the border areas of Pakistan and Afghanistan.…”
Section: Discussionmentioning
confidence: 99%